The Influence of Organizational Commitment and Perceived Organizational Support of BPKP in Achieving the Vision of Indonesia Emas 2045 Moderate By Leadership Transformation - Yanson Bastian; Iwan Kresna Setiadi; Yudi Nur Supriadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aims to analyze the influence of Organizational Commitment and Perceived Organizational Support on the achievement of the Golden Indonesia 2045 Vision within the BPKP environment, with Leadership Transformation as a moderating variable. The dynamic nature of change and the high demands for adaptation in realizing the national development vision place BPKP in a strategic position. However, the success of this adaptation heavily depends on individual readiness and organizational support. This study examines how employees' readiness to face change and their perceptions of organizational support can drive the achievement of these long-term goals. Furthermore, Leadership Transformation characterized by the ability to inspire, drive change, and align team efforts with organizational vision—is hypothesized to strengthen or weaken the relationship between Organizational Commitment and Perceived Organizational Support with the achievement of the Golden Indonesia 2045 Vision. A quantitative approach using surveys will be employed to collect data from BPKP employees. The data obtained will then be analyzed using the Structural Equation Modeling Partial Least Squares (SEM-PLS) method. The results of the study indicate that Organizational Commitment and Perceived Organizational Support have a positive and significant effect on the effectiveness of transformation towards the Golden Indonesia 2045 Vision. Moreover, Leadership Transformation has been proven to strengthen the influence of these independent variables, meaning that high levels of commitment and support, combined with transformational leadership qualities, will enhance BPKP's success in achieving the goals of Indonesia Emas 2045.